Explaining the entrepreneurial orientation performance relationship in emerging economies: The intermediate roles of absorptive capacity and improvisation - Hughes, Paul; Hodgkinson, Ian R.; Hughes, Mathew; Arshad, Darwina (Springer, 2017)
Research has established the relevance of entrepreneurial orientation (EO) to firm performance but skepticism remains because of the ambiguity surrounding how EO might improve firm performance. We examine the key concepts of absorptive capacity and improvisation as two alternative learning modes serving as intermediate steps between EO and firm performance. Locating our study within manufacturing SMEs in Malaysia, we find that absorptive capacity enhances the EO–performance relationship, both as a moderator and a mediator. In contrast to expectations, however,improvisation showed no such effects but conferred its own separate benefits instead. We further discuss the different effects of these learning modes on high performance and low performance groups.